Anisotropic strengthening of nanotwin bundles in heterogeneous nanostructured Cu: Effect of deformation compatibility. (15th May 2021) - Zhao, H.Z.; You, Z.S.; Tao, N.R.; Lu, L.
Abstract: Anisotropic tensile behaviors of a heterogeneous nanostructured Cu composed of isotropic nanograin matrix and anisotropic nanotwin bundles were investigated under loading directions parallel, normal, and 45° inclined to the twin boundaries (TBs). Distinct from the anisotropic strengthening effect in the homogeneous nanotwinned (NT) counterpart, the heterostructure exhibits the highest strength under parallel tension, and moderate strength under normal tension. High-resolution digital image correlation analysis indicated an orientation-dependent deformation compatibility between the nanotwin bundles and nanograin matrix, i.e., compatible deformation in the parallel orientation; but significant incompatibility in orientations both normal and 45° inclined to TBs. The results reveal that the strengthening effect of nanotwins in heterogeneous nanostructure is not only dependent on the strength of themselves, but also influenced by the deformation compatibility with surrounding components. The orientation-dependent deformation compatibility was attributed to the interactions between isotropic shear bands in nanograin matrix and anisotropic deformation in nanotwin bundles. Graphical abstract: Image, graphical abstract